2017
DOI: 10.3389/fmicb.2017.00849
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Root Microbiome of Plants Growing in Oil Sands Reclamation Covers

Abstract: Oil sands mining in northern Alberta impacts a large footprint, but the industry is committed to reclaim all disturbed land to an ecologically healthy state in response to environmental regulations. However, these newly reconstructed landscapes may be limited by several factors that include low soil nutrient levels and reduced microbial activity. Rhizosphere microorganisms colonize plant roots providing hosts with nutrients, stimulating growth, suppressing disease and increasing tolerance to abiotic stress. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 89 publications
1
50
0
Order By: Relevance
“…Plant-associated microbiomes play a role in determining plant fitness ( 1 , 2 ), and it is well established that the composition of the plant microbiome is influenced by many host-associated and environmental factors ( 3 – 12 ). Recent research has demonstrated that changes in soil moisture availability have significant effects on plant-associated microbiomes ( 13 , 14 ).…”
mentioning
confidence: 99%
“…Plant-associated microbiomes play a role in determining plant fitness ( 1 , 2 ), and it is well established that the composition of the plant microbiome is influenced by many host-associated and environmental factors ( 3 – 12 ). Recent research has demonstrated that changes in soil moisture availability have significant effects on plant-associated microbiomes ( 13 , 14 ).…”
mentioning
confidence: 99%
“…According to the OTU information, mothur (version v.1.30.1) was used to calculate the alpha diversity index (Chao 1, ACE, Shannon, Simpson) [86], and curves were generated with the R language tool [87]. Beta diversity analysis was represented by Bray-Curtis distance matrices generated from the OTU table, and statistical analysis and mapping was performed with PCoA in R language [88]. The community structure composition of different classification levels (such as phylum, genus and OTU) was obtained by taxonomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For both culture-dependent and independent community composition, we found that Gammaproteobacteria, particularly those genera from family Enterobacteriacea dominated the plant endospheric communities regardless of plant host species and contamination. Genera from family Enterobacteriaceae was also found to predominate the endosphere rather than the rhizosphere of plants in Athabasca oilsands reclamation sites (Mitter et al, 2017 ). Gammaproteobacteria was also reported to be predominant in the endosphere of ginseng plants (Khan Chowdhury et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%